The Analysis of the Student Payment Information System at Madrasah Ibtidaiyah Mafaatikhul Huda Penarukan - Raya, Mohamad Bintang Jagad; Krishantoro, Wahyu (Media Jurnal Informatika, 2025)
The student payment information system is an essential component in managing educational administration, particularly in primary-level institutions such as Madrasah Ibtidaiyah (MI) Mafaatikhul Huda Penarukan, located in Penarukan Village, Adiwerna District, Tegal Regency, Central Java Province. The purpose of this study to examine the current payment information system and provide an overview of its strengths, weaknesses, opportunities, and threats through a SWOT analysis of the manual system currently in use. This research employs a qualitative method, with data collected through observation, interviews, and library research. The analysis follows a four-stage method: surveying the existing system, analyzing or evaluating the survey results, identifying the current system’s needs, and specifying system requirements to support appropriate and relevant development. The finding indicate of the payment process is still manually, which is considered less effective due to a high risk of data loss and delays in recordkeeping. Therefore, the development of an integrated digital payment information system is needed to improve speed, accuracy, and transparency in administrative processes. This study is expected to serve as a foundation for recommending the modernization of financial administration systems at MI Mafaatikhul Huda Penarukan.